Exploring Students’ Levels of Oral Presentation Apprehension in ESL Context - Ibrahim, Qistina (AJELP: Asian Journal of English Language and Pedagogy, 2024)
The study was aimed to investigate ESL students’ levels of oral presentation apprehension. All postgraduate students from Faculty of Education of a public university in Malaysia participated in this study. It is a qualitative study, and data needed for the study were extracted from McCroskey’s Personal Report of Public Speaking Anxiety (PRPSA). The participants answered 34 Likert-scale items, and the data were analysed by using PRPSA scores formula. Participants who scored more than 131 were considered to have a high level of oral presentation apprehension, and those who scored below than 98 were considered to have a low level of oral presentation apprehension. Besides, the moderate level of oral presentation apprehension was determined by the number of scores ranged from 98 to 131. Descriptive analysis was also performed by using SPSS. The findings reveal that overall, the participants have a low level of oral presentation apprehension. 66.7% of the participants had a low level of oral presentation apprehension, 29.2% had a moderate level of oral presentation apprehension, and only 4.2% had a high level of oral presentation apprehension. Furthermore, it was reported that the external and internal effects of oral presentation apprehension experienced were rated negatively by the participants. However, the scores for the internal effects were higher compared to the external effects. This is believed due to the participants’ high exposure to the oral presentation activity and pedagogical trainings as well as their language proficiency.